2012
DOI: 10.1161/jaha.112.002238
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Restricts Multipotency of Mesenchymal Stem Cells and Impairs Their Capacity to Augment Postischemic Neovascularization in db/db Mice

Abstract: BackgroundThis study tested the hypothesis that type 2 diabetes restricts multipotency of db/db mesenchymal stem cells (MSCs), promotes their terminal differentiation into adipocytes rather than endothelial cells, thereby promotes adipocytic infiltration into ischemic muscles, and reduces their capacity to participate in postischemic neovascularization.Methods and ResultsTo test this hypothesis, we transplanted MSCs from db/db or wild-type (WT) mice into WT recipients after induction of hind limb ischemia. WT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
63
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 34 publications
11
63
2
Order By: Relevance
“…This is consistent with previous studies showing that hyperglycemia can promote adipogenic differentiation of muscle-derived stem cells (27). Interestingly, cardiac-derived cells with a mesenchymal phenotype are capable of differentiating into an adipocyte lineage in vivo (22,93), and fibroadiposis has been suggested to be a disease of CPCs "gone awry" that occurs when they differentiate into adipocytes (94). With respect to diabetes, hyperglycemia has been shown to decrease the activity of GAPDH, which metabolizes GAP to 3-phosphoglycerate.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with previous studies showing that hyperglycemia can promote adipogenic differentiation of muscle-derived stem cells (27). Interestingly, cardiac-derived cells with a mesenchymal phenotype are capable of differentiating into an adipocyte lineage in vivo (22,93), and fibroadiposis has been suggested to be a disease of CPCs "gone awry" that occurs when they differentiate into adipocytes (94). With respect to diabetes, hyperglycemia has been shown to decrease the activity of GAPDH, which metabolizes GAP to 3-phosphoglycerate.…”
Section: Discussionsupporting
confidence: 93%
“…Although it is unlikely that differentiation of CPCs contributes directly to myocardial regeneration, differentiation of stem cells has been suggested to reflect their capacity to invoke reparative responses in injured tissue (22,45). Therefore, we next examined gene programs that might indirectly regulate their restitutive actions during cell therapy.…”
Section: C and D)mentioning
confidence: 99%
“…of MSC donor and/or recipient may negatively affect efficacy and potency of the cellular products (52), and whether these effects can be reverted under the appropriate conditions ( i.e ., in vitro culture and/or in vivo treatments)(53-57). …”
Section: Introductionmentioning
confidence: 99%
“…BM-MNCs are also capable of increasing angiogenesis with critical limb ischemia in humans (54). However, several studies have now shown that the effectiveness of BM-MNC transplantation can depend on the health of the donor with demonstration of BM-MNC dysfunction observed in cardiovascular disease (57), heart failure (26), and type 2 diabetes (16,58).…”
mentioning
confidence: 99%